The concept of the personal and axiological experience in the philosophy of K. Wojtyła – John Paul II: a starting point of philosophical anthropology - Jerzy Krzanowski (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
Philosophy, which reflects different anthropological solutions and theories of humanity, considered in the perspective of Christian philosophical anthropology in Poland, is the Thomistic phenomenology of action of K. Wojtyła – John Paul II. In this philosophical concept the starting point is the personal and axiological experience. It is analysis of the acts of conscious action. Act reveals the person (the moral significance of the person). Widely understood Wojtyla’s Personalism is a chance of a creative meeting for two philosophies – from Lublin and Cracow. The more the use of his thoughts, the more developed they become.